2005
DOI: 10.1177/0363546504271509
|View full text |Cite
|
Sign up to set email alerts
|

Operative Stabilization of Posterior Shoulder Instability

Abstract: In the case of traumatic posterior shoulder subluxation, posterior lesions of the labrum ("reverse Bankart"), articular edge, and capsule are observed. Surgical treatment addressing these lesions led to satisfactory results for both the open and arthroscopic treated groups. In this study, an arthroscopic technique utilizing suture anchor repair with capsular placation provided the most favorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 32 publications
3
124
0
4
Order By: Relevance
“…Additionally, the level 4 retrospective investigation of 20 shoulders performed by McIntyre et al [13] utilized a multiple suture technique and reported 60% (3 of 5) of their DeLong JM et al . Posterior shoulder instability in the athletic population Bottoni et al [32] Ⅳ CLR TC (1 bilateral)…”
Section: Concomitant Injuriesmentioning
confidence: 99%
“…Additionally, the level 4 retrospective investigation of 20 shoulders performed by McIntyre et al [13] utilized a multiple suture technique and reported 60% (3 of 5) of their DeLong JM et al . Posterior shoulder instability in the athletic population Bottoni et al [32] Ⅳ CLR TC (1 bilateral)…”
Section: Concomitant Injuriesmentioning
confidence: 99%
“…Subluxation in this scenario is an incomplete dislocation event that spontaneously reduces. Posterior shoulder instability is typically the result of a posteriorly directed load to the shoulder in a position of forward flexion, adduction, and internal rotation [3]. Posterior shoulder instability, including dislocation and subluxation, occurs much less frequently than anterior Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%
“…Open treatment with labral repair and capsular shift have been described with variable results. [8][9][10] More recently, arthroscopic techniques have shown good results. [1][2][3][4][5][6][7] Although most surgeons are comfortable with anterior labral repair, arthroscopic procedures about the posterior glenoid and capsule can be more difficult because of their relative infrequency.…”
Section: Discussionmentioning
confidence: 99%